If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -33 = -2a + a Combine like terms: -2a + a = -1a -33 = -1a Solving -33 = -1a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'a' to each side of the equation. -33 + a = -1a + a Combine like terms: -1a + a = 0 -33 + a = 0 Add '33' to each side of the equation. -33 + 33 + a = 0 + 33 Combine like terms: -33 + 33 = 0 0 + a = 0 + 33 a = 0 + 33 Combine like terms: 0 + 33 = 33 a = 33 Simplifying a = 33
| (5x-2)(x-1)=x(2x+1) | | 2ln(x)=ln(4)+ln(x+3) | | 9x-2=3x+70 | | (5x-2)(x-1)=x(x+1) | | 2a-3(3a-5)=7a+6 | | 4y+8=2y-6 | | -4x^2+5x+100=0 | | X^2=.064 | | 3(5-3t)+5t=-2t-7 | | 15x+12x+17=180 | | 13-2n=4+n | | 2x^4+3x^3-4x^2-x+14=0 | | 4y+2-y=6 | | 2x+5(x-10)=-1 | | 3(5x+2)-(9x-8)=7(x+12) | | 2x^4+3x^3-4x^2-x+14=-12 | | 3x-2=18-2x | | -2x+5(x-10)=-1 | | 5(5-1)+-3125-7= | | 3b^2+5b= | | 5x^4+4x^3= | | 5r+3f=12 | | 20-12=4(x-1) | | (x-3)(2x-5)+6=2x^2-12 | | -6x-2=4x-1 | | 18w-2-10w+14= | | 6p^4-486p^2= | | 9x^2+27x-7=0 | | 12x^2-6x-3=3-5x | | f(x)=2x^2+20x+49 | | sin(2x-30)=cos(3x+5) | | (-7-3m^3-3m^4)+(-8m-8m^3-m^4)= |